Financial Innovation and Restriction Hypothesis in the Banking Industry: Evidence from ASEAN- 5 - Bustaman, Yosman; Viverita, Viverita; Lingga, Margaretha TP; Siahaan, Antonius P. (The Indonesian Capital Market Review, 2023)
This study investigates the financial innovation impact on bank market power in ASEAN banking from 2008 to 2018. It uses income diversification as a representative of financial innovation. The im- pact of countries’ development of financial innovation on market power is measured by the number of ATM, internet, and cellular phone users. The data panel regression model reveals that diversified banks may enjoy higher market power. This result rejects the banking restriction activity hypothesis, which states that a bank that diversifies its income stream results in increased competition. A higher number of available ATMs and more internet users lowers the percentage disparity of price and marginal cost and consequently increases the market competitiveness. Nevertheless, an increasing number of cellular users in the country increases market power. Conjecturally, more people use the online bank platform on their cellular phones, which creates a greater flow of fees to the bank.